Perfo-3 : "Een soort schoonheid". - Brett, Guy (Rotterdam : Lantaren Venster, 1985)
Alvaro, Egidio ; Baren, Peter ; Burmester, Gerardo ; Babel, Tara ; Buthe, Michael ; Baquié, Richard ; Carcasonne, Shirley ; Chenard, Laure ; Dalstra, Koos ; Droparchief ; English, Rose ; Etter, Olivia ; Fiala, Natascha ; D'Hellemes, Claudine ; Hoeven, Rob & Ed Van der ; Jongsma, Hans ; Kawazu, Marie ; Krist, Suzanne ; Krempelsauer, Joseph ; Kramer, Michael ; Meziat, Catherine ; De Marez, Cas ; Michel, Johnny ; Duijfjes, Lisa Marcus / Barbara ; Oorebeek, Willem ; Prins, Lieve ; Prinsen, Yolanda ; Pons, Flavio ; Polke, Sigmar ; Lotsy, Liesbeth Pallesen / Henk ; Reedy, Carlyle ; rahs, Wolfgang ; Smits, George ; Seagrave, Anne ; Sevol, Reinhard U. ; Spiller, Giorgio ; Talman, Stefi ; Ukeles, Mierle ; Vissers, AB ; verkerk, Hans ; Warburton, Holly ; Wolff, Carl Emanuel ; Fischli & Weiss
Perfo-3 : "Een soort schoonheid", LantarenVenster, Rotterdam, 11 mei - 18 mei 1985
Engels & Nederlands
boek